Pengaruh Core Endurance Training Terhadap Perbaikan Postur Pada Anak Sekolah Menengah Pertama 2 Colomadu - Ratnawati, Dyah, Maskun Pudjianto, S.Pd.,M.Kes (2016)
Background: Every day, school children carry books and school supplies when going to and from school. Backpack is one of the alternative places that can be used to carry books and school supplies. More than 57% of children use a backpack weigh more than a standard user. The use of a backpack that is not appropriate to have a negative impact on students, including posture disorders because the wrong attitude. To overcome the problem of posture one can do core endurance training. The Objective of Research: To determine the effect of endurance training on the improvement of core posture Junior High School 2 Colomadu children. The Method of Reserch: This in study the authors use this type of research preexperimental research design pretest-posttest control group design compared betwen 2 group namely, the treatment group were given core endurance training and the control group was not given core endurance training performed for 8 weeks is done 2x a week with 30 sessions exercise. Measurement of posture using inclinometer. Data analysis techniques in this study using the Wilcoxon test and Mann Whitney influence to test different influences. Result of Reserch: Based on this research, the effect of endurance training with no core by core endurance training, using the Wilcoxon test. Namely, core endurance training with the result p = 0.000451 mean p <0.05 can be concluded no effect on posture improvement, and not by core endurance training with the result p = 1.0 means p> 0.05dapat concluded no effect on posture improvement. As well as the influence of different test results between providing core endurance training with endurance training without giving cores using Mann Whitney test with p = 0.000002 meaningful results p, 0.05 can be concluded there is a difference between the effects of endurance training with core without core endurance training on the improvement of posture. Conclucion: The provision of core endurance training is proven to give effect to changes in posture in children SMPN 2 Colomadu